Chapter A cultura na Europa humanista de David Sassoli: reflexões sobre o projeto das Capitais Europeias da Cultura (CEC) - Sidoncha, Idalina (Libere carte, 2023)
Europe, as the title of this collective book indicates, is a project under construction and David Sassoli, who is honored here, one of its most striking and memorable builders. European construction, despite all the deviations and hesitations that distinguish every single genuine human situation, has been based on a set of values that represent our own identity, in the full recognition of all the differences that simultaneously nourish it. Culture has progressively played a major role in this lasting European undertaking. In this chapter, by honoring a man who hoped for a better spiritual condition for Europe, we reassess one of the main instruments for establishing a cultural path in Europe: the European Capital of Culture (ECOC) project. The record and the tone of the following pages is far beyond the usual scope of mere description. Guided by the inspiring example of Sassoli, we face up to suggest a set of measures that will allow the ECOC action to fully meet its purpose, thus contributing to make the cultural option in Europe truly irreversible.